Comparison of efficacy of acupuncture-related therapy in the treatment of perimenopausal obesity: a network meta-analysis of randomized controlled trials - Wang, Lu; Lu, Tianrui; Tu, Luxuan; Zhuang, Jiamei; Xu, Yunxiang; Chen, Guizhen (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to compare the effects of acupuncture-related therapies on obese perimenopausal women through a systematic review and network meta-analysis (NMA) of randomized controlled trials (RCTs).MethodsEmbase, MEDLINE, the Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang Data, Chongqing VIP, and SinoMed were systematically searched from the inception to December 2024. The certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) framework. Primary outcomes included body mass index (BMI) and body weight. Secondary outcomes included waist circumference (WC), body fat percentage, the Kupperman index, estradiol (E2), follicle-stimulating hormone (FSH), luteinizing hormone (LH), triglyceride (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL).ResultsEighteen RCTs involving 1268 patients with perimenopausal obesity were included. The results of the network meta-analysis revealed that, when compared to traditional Chinese herbal medicine (HM) and Western medication (WM), multiple acupuncture therapies demonstrated superior efficacy on the overall clinical effectiveness. The analysis showed that acupoint catgut embedding demonstrated superior BMI, weight, the Kupperman index, and estradiol levels improvement. Electroacupuncture was most effective for WC reduction but was inferior to sham acupoint catgut embedding for BMI and weight. Warm needle acupuncture ranked highest for body fat percentage. The pairwise meta-analysis demonstrated that acupoint catgut embedding significantly reduced FSH and LH levels. The descriptive analysis suggested that acupoint catgut embedding and warm needle acupuncture were associated with improvements in TG and LDL Levels.ConclusionThe results showed that the acupuncture-related therapies can benefit patients by improving obesity indicators, perimenopausal symptoms, serum sex hormone levels, and blood lipid levels. Several acupuncture-related therapies may be more effective than WM or HM for perimenopausal obesity and could serve as alternative treatments, with method selection based on individual clinical needs, though confirmation through higher-quality trials is warranted.Systematic review registrationhttps://www.crd.york.ac.uk, identifier CRD42024516232.